Typological analysis of the dynamic characteristics of overflows under homogeneous urban form: evidence from Hong Kong’s back alleys - Da Du; Yuhan Gao; Xinpeng Wang; Nobuaki Furuya (Journal of Asian Architecture and Building Engineering)
Urban form refers to the geometric characteristics of a city in two- and three-dimensional space. Homogeneous urban forms often weaken regional characteristics, leading to a decline in urban vitality, among other issues. However, research has generally focused on fixed elements, such as buildings and streets, while paying less attention to semi-fixed elements, such as “overflow” (i.e. movable personal items that people place in public spaces), which plays a crucial role in shaping urban form. This study aims to explore the characteristics of overflow forms in urban spaces. Using a typological approach, it classifies overflows in Hong Kong’s back alleys. The Pearson chi-squared test examines the relationship between position and internal arrangement of overflows, while the Kruskal – Wallis and Nemenyi tests assess the differences in scale among various types of positions and internal arrangements. The findings reveal the dynamic characteristics of overflows, offering insights into how urban residents personalize public spaces in response to challenges and opportunities presented by governmental regulations and the built environment. By introducing new perspectives and research objects into the study of urban form, this study provides valuable ideas for micro-scale urban design and mitigating the homogeneous urban form.